AGRICULTURAL RESOURCES AND DEVELOPMENT PRIORITIES OF THE MUNICIPALITY OF STARA PAZOVA - Mihailović, Branko; Simonović, Zoran; Ćurčić, Nikola (Economics of Agriculture, 2017)
This paper examines the agricultural potentials of Stara Pazova, and consequently defnes development priorities in this area. The aim at the research is to assess the real possibilities for improvement on agriculture Municipality. The analysis is focused on: knowledge transfer and innovation, agriculture technical equipment, warehouse and fnishing capacities in agriculture, processing of agricultural products and the vision and development priorities over agriculture Municipality. The research results show that the improvement to the competitiveness of the agricultural sector of Stara Pazova requires the implementation of adequate policy measures and projects related to the improvement to human resources, higher level of processing of agricultural and food products, as well as better agricultural technical equipment agricultural producers. Activities in this area include primarily higher correlation science and practice across the reorganized agricultural station, extension services, home service , agricultural cooperatives and other associations of farmers; development and implementation of new knowledge and skills of farmers through advice, training, seminars, courses; support young farmers in the modernization of farms. All projects in this feld must be based on adequate state support and coordinated efforts of the public and private sectors.